2014
DOI: 10.1136/bcr-2013-200714
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic management of midgut malrotation and tuberculous peritonitis in an adolescent boy

Abstract: An unusual case of miliary plastic peritonitis associated with midgut malrotation in an adolescent in whom various diagnostic investigations, medical management and staged initial laparoscopic diagnostic followed by therapeutic procedure was curative have been presented. Tuberculous miliary plastic peritonitis causes dense adhesions between bowel loops and prevents midgut volvulus in a pre-existing malrotation. Diagnosis can be a challenge and threshold for diagnostic laparoscopy should be low. Interval correc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“…Eleven of the 19 cases of peritoneal TB could be further divided into one of the three types 14 20 21 23 25 26 29. Nine (82%) had a predominantly fibrotic type and two (18%) had a predominantly dry type.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Eleven of the 19 cases of peritoneal TB could be further divided into one of the three types 14 20 21 23 25 26 29. Nine (82%) had a predominantly fibrotic type and two (18%) had a predominantly dry type.…”
Section: Resultsmentioning
confidence: 99%
“…Steroids in addition to antituberculous drugs were started in seven cases 8 14 29. Follow-up data were available for two of these cases, ranging from 9 months to 6 years 14 29.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, it took about 2 weeks to set the peritoneal TB diagnosis in our patients. Additionally, the peritoneal TB diagnosis for children is rarely suspected only upon clinical presentation [12]. As this study shows, the most common observed symptoms were unspeci c and very common for every sick child: abdominal pain with distention and fever.…”
Section: Discussionmentioning
confidence: 89%
“…These were the reasons why we conducted this systematic review and analysis. As our study shows, individual cases of peritoneal TB in children are observed in regions with a different morbidity of TB, social and economic status including experience of four different continents -most of cases presented from India (11), Tunisia (11) and Turkey (10) and others from Saudi Arabia, Italy, Germany, United Kingdom, Canada, Taiwan and United States of America [3,4,[7][8][9][10][11][12][13][14][15].…”
Section: Discussionmentioning
confidence: 99%